Implementasi Metode Bubble Sort Descending pada Aplikasi Sealed Bid Auction Toko Indonesia Art Shop - Syuhada, Muhammad Randa; Samsudin (LPPM Universitas Mulia, 2025)
Indonesia Art Shop is a shop that sells all kinds of antiques for collection, these collectibles range from small to large. Small items such as: rings, coins, agate, ancient money and large items such as clocks, old school radios, typewriters, paintings, urns, etc. This research aims to design a sealed bid auction application that is useful to facilitate and benefit Indonesia Art Shop shop owners in selling antiques. By implementing the bubble sort descending method in the sealed bid auction application which aims to assist in sorting data from the highest bid to the lowest bid, so that it can be implemented in the application and make it easier for the admin to determine the winner of the auction, the system automatically determines the winner with the highest bid, the application also uses a closed auction system or sealed bid auction which is useful for maintaining user confidentiality in bidding for antiques made by users or bidders. With the creation of a web-based sealed bid auction application at the Indonesia Art Shop store as a medium for selling antiques with a closed auction system, so it is hoped that antiques are sold at the highest price among the antique collector market and also as a promotional medium to expand the market.